Crohn's Disease Recent Advances - Ahmed, Monjur (IntechOpen, 2021)
This book discusses the extra-intestinal manifestations of Crohn's disease, recent advances in the diagnosis and treatment of Crohn's disease, the role of partial enteral nutrition and apheresis in Crohn's disease, and how Crohn's disease is treated in Chinese medicine. This book is a useful reference for practicing physicians who treat Crohn's disease.